THE RELATİONSHİP BETWEEN JOB SATİSFACTİON AND AFFECTİVE COMMİTMENT AMONG ADMİNİSTRATİVE STAFF İN SAUDİ ARABİA - Rajeh Bati Almasradi; Siti Aisyah Panatik; Nurul Farhana Noordin (Psycho Idea, 2020)
Previous researches revealed that there is a relationship between job satisfaction and commitment which in turn benefit the workplaces positively. Organizational commitment consisted of three dimensions, namely affective, commitment, continues commitment, and normative commitment. Job satisfaction has been considered as an important predictor to enhance affective commitment among employees.  Therefore, the purpose of this paper is to look at the relationship between job satisfaction and affective commitment among employees of higher learning institutions of Saudi Arabia. This paper employed survey method in collecting data from a sample of 373 administrative employees selected from Saudi Arabian universities., which will further the understanding of the link between affective commitment and job satisfaction. The data were analyzed using descriptive, correlation and regression through SPSS Version 23. The findings of this paper indicate that job satisfaction has a positive effect on affective commitment at higher learning institutions of Saudi Arabia. This paper also provides discussion on the practical implication of this study toward the higher learning institution in Saudi Arabia.